A climate Encouraging the Growth and Flourishing of Monkeypox in Indonesia - Ramadhan Tosepu; Effendy, Devi Savitri; Nasaruddin, Nasaruddin; Asriati, Asriati; Yusran, Sartiah (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Introduction: Climate change has significant impacts on human health and has the potential to trigger the emergence of various diseases by changing temperature, rainfall, wind patterns, and sunlight exposure. These changes create environmental conditions that support the survival, reproduction, and spread of disease-causing agents, such as viruses and bacteria. Adaptation of disease agents to these changes increases the risk of disease spreading in the community. In addition, climate change also expands the range of some disease agents, which were previously limited to certain areas, thus having a wider impact. Low temperatures (10–25°C), high humidity (?70%), and limited sunlight (UV index <6) promote the environmental persistence of the monkeypox virus, whereas high temperatures (>30°C) and UV exposure (290–320 nm) accelerate its degradation, influencing transmission patterns and infection risk in humans and animals. Methods: This study examines the climate conditions that may support the development of monkeypox in Jakarta. The main focus of this study is to identify climate factors, such as temperature, humidity, and rainfall patterns, that allow the spread of monkeypox virus. Climate data are analyzed to understand how these conditions play a role in increasing the risk of monkeypox virus transmission, both from animals to humans and between humans. Results: Our findings indicate a minimum temperature of 27.96°C, a maximum of 33.74°C, and an average of 30.11°C. The average humidity was 74.21%. The duration of sunlight ranged from a minimum of 7.30 hours to a maximum of 9.60 hours. Conclusion: Climate factors are key triggers in the development of Monkeypox within the environment. Specific temperature and humidity levels can create favorable conditions for the spread of the Monkeypox virus in certain regions. Additionally, extreme climate fluctuations may influence the spread patterns and severity of the disease, underscoring the importance of understanding how environmental conditions affect the transmission of diseases like Monkeypox.